Pembentukan Karakter Menurut Ki Hajar Dewantara dan Relevansinya dengan Pendidikan Islam - Miftahus Salam (Universitas Islam Lamongan, 2019)
Character building is an integral part of the main objective of education. Not only related to the development of scientific insights, but Islamic education is also oriented to the formation of morals (character). In Indonesia, the educational figure Ki Hajar Dewantara has a unique perspective on education and its strategy in shaping students' character. In this research, several problem formulations are proposed, including 1) what is the method of character building according to Ki Hajar Dewantara ?, 2) How is the character-building method in Islamic education? This type of research is research (Library Research), which takes library materials that have something to do with the problem under study. This research concludes that character education, according to Ki Hajar Dewantara consists of among, ngemong and among as well as ngerti, ngrasa and nglakoni. Meanwhile, its relevance to Islamic education is the concept of character building Ki Hajar combining morality, intellect and spirituality, the three of which are circularly applicable in the concept of Islamic faith, which is not only limited to believing and understanding, but also implementing it in everyday life